Role of Digital Media in Oral Health Awareness: A Review Article - Umesh Kempraj; Preethivarthana M; poongodi v; vinu sarangesh (International Journal of Community Dentistry, 2026)
Oral diseases remain a significant global public health concern, affecting a large proportion of the population and impacting overall quality of life. Limited awareness, socioeconomic disparities, and inadequate access to dental care contribute to the high burden of oral conditions . In recent years, digital media has emerged as an innovative approach to disseminate health information and promote preventive practices in oral health. A narrative review was conducted using previously published literature focusing on the role of digital media in oral health awareness. Relevant studies, systematic reviews, and scoping reviews were identified from indexed journals and academic sources. The review included articles addressing social media, mobile health applications, tele-dentistry, and online educational platforms in oral health promotion. The findings indicate that digital media plays a crucial role in improving oral health knowledge, attitudes, and practices among diverse populations. Social media platforms and mobile applications enhance patient engagement and encourage positive behavioral changes such as regular brushing and dental visits. Additionally, targeted digital interventions have shown effectiveness in specific groups, including children and pregnant women. However, challenges such as misinformation, lack of regulation, and digital inequality remain significant barriers. Digital media is a powerful and cost-effective tool for promoting oral health awareness and facilitating behavior change. While it offers substantial benefits in terms of accessibility and engagement, addressing issues related to content accuracy and digital access is essential. Strategic implementation and regulation of digital platforms can enhance their potential in improving global oral health outcomes .